دراسة وتحليل أثر هجمات الحرمان من الخدمة Denial of Service على شبكات الـZigBee ذات الطوبولوجيا الشجرية (Tree) بالمقارنة مع الطوبولوجيا المختلطة (Mesh) من خلال معايير(التأخير، الحمل، والإنتاجية) - أحمد أحمد; لجين صقر (Tishreen University, 2018)
ZigBee networks have revolutionized industrial control, remote data collection and intelligent home automation as they rely on ZigBee, a wireless data transmission technology designed to meet the unique needs of wireless sensor networks such as low power consumption and low transmission rates to maintain Battery life is longer, and is based on IEEE 802.15.4 Security is one of the fundamental issues of any network, and the study of attacks and their impact of the important and necessary, The most serious of these attacks Denial of Service Denial of Service, is an attack aimed at denial of service and attempt to make this service unavailable or delayed access to the users concerned. The aim of this study is to analyze the impact of denial-of-service attacks on ZigBee networks with tree topology and mesh topology, and compare them through criteria: delay, load, and throughput, as they are the most important metrics determining the performance and effectiveness of the network . The study was carried out using OPNET 14.5 simulation tool, which is one of the most important programs used in the modeling and simulation of wired and wireless networks, and to conduct many experiments and compare them through the mentioned metrics. The results showed that the attack on  ZigBee network lead to different damages depending on the topology, so we have studied and analyzed the impact of denial of service attacks on two different types of topologies, Tree and mixed (Mesh), since these two topologies give certain results in the absence of an attack and different results in case of attack on them. أحدثت شبكات ZigBee تحولاً جذرياً في ميدان التحكم الصناعي, وجمع البيانات عن بعد, وأتمتة المنازل الذكية حيث أنها تعتمد على ZigBee وهي تقنية لنقل البيانات في شبكة لاسلكية, و مصممة لتلبية الاحتياجات الفريدة لشبكات الاستشعار اللاسلكية مثل استهلاك منخفض للطاقة, ومعدلات نقل منخفضة, للحفاظ على عمر البطارية أكبر وقت, وتعتمد على المعيار IEEE 802.15.4 . الأمن هو من القضايا الاساسية لأي شبكة, ودراسة الهجمات وتأثيراتها من الأمور الهامة والضرورية, ومن أخطر هذه الهجمات هجوم الحرمان من الخدمةDenial of Service , هو هجوم يهدف الى الحرمان من الخدمة و محاولة جعل هذه الخدمة غير متوفرة أو تصل متأخرة إلى المستخدمين المعنيين بها. إن هدف هذه الدراسة هو تحليل أثر هجمات الحرمان من الخدمة على شبكات الـ ZigBee ذات الطوبولوجيا الشجرية (Tree), والطوبولوجيا المختلطة (Mesh) , والمقارنة بينها من خلال المعايير: التأخير, الحمل, والإنتاجية, حيث أنها من أهم المعايير التي تحدد أداء وفعالية الشبكة. تمت الدراسة باستخدام أداة المحاكاة OPNET 14.5 الذي يعتبر من أهم البرامج المستخدمة في نمذجة ومحاكاة الشبكات السلكية واللاسلكية, والقيام بالعديد من التجارب ومقارنتها من خلال المعايير المذكورة. حيث أظهرت النتائج أن الهجوم على شبكة الـZigBee يؤدي الى أضرار تختلف باختلاف طوبولوجيتها, لذلك قمنا بدراسة وتحليل أثر هجمات الحرمان من الخدمة على نوعين مختلفين من الطوبولوجيات وهي الشجرية (Tree) والمختلطة (Mesh), حيث أن هاتين الطوبولوجيتين تعطيان نتائج معينة في حالة عدم وجود هجوم ونتائج مختلفة في حالة الهجوم عليها.